(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The work deals with the responsibility of the Public Attorney for their performance in public procurement. To this end, it is necessary to investigate the system of responsibility adopted by Law 14,133/2021, as well as to evaluate the role of this professional, according to the provisions contained in the aforementioned legislation and previous legislation to reach the main focus of the work, which deals with the responsibility of the Public Prosecutor when issuing legal opinions, in light of doctrine, jurisprudence, and pertinent legislation. The research hypothesis is to verify which spheres of responsibility and to what extent this occurs due to the performance of the negligent Public Attorney who allows deviations and acts of corruption to go unnoticed. The theme is relevant to demonstrate the importance of preventive legal counsel for good contracting, as well as to establish security parameters for such public servants. The contribution relates to the debate about the immunity of the public attorney by reason of the issuance of legal opinions within the scope of acquisitions and contracting by the State. It is emphasized that the New Bidding Law innovated several aspects of the bidding procedure, with the role of the legal advisor responsible for issuing opinions being considerably reshaped. The conclusion is that the Public Attorney is not immune for their negligent or fraudulent actions, under the argument that their sight is a opinion, and the system provided for in the LINDB must be applied. The research used the hypothetical-deductive method and bibliographic research.